2005
DOI: 10.2519/jospt.2005.35.10.645
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Diagnosis of Vertebrobasilar Insufficiency: Resident's Case Problem

Abstract: Study Design: Resident's case problem. Background: Vertigo and visual disturbances are common symptoms associated with vertebrobasilar insufficiency (VBI), but the physical examination procedures to verify the existence of VBI have not been validated in the literature. The objective of this resident's case problem is to demonstrate how a patient's complaint of vertigo and visual disturbances, combined with positive clinical examination findings, can be a potential medical screening tool for VBI. Diagnosis: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The VAT certainly fi ts this description and is commonly used in clinical practice as a screening test for VBI despite controversy surrounding this test [25][26] . Cote et al 20 measured vascular impedance on 42 subjects with Doppler ultrasonography while in the VAT position and determined the sensitivity and positive predictive values of the VAT to be zero.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The VAT certainly fi ts this description and is commonly used in clinical practice as a screening test for VBI despite controversy surrounding this test [25][26] . Cote et al 20 measured vascular impedance on 42 subjects with Doppler ultrasonography while in the VAT position and determined the sensitivity and positive predictive values of the VAT to be zero.…”
Section: Discussionmentioning
confidence: 98%
“…Asavasopon et al 25 reported that patient symptoms consistent with VBI were produced while performing the VAT and the patient was referred for further diagnostic imaging. Results from both ultrasonography and MRA confi rmed 80% to 90% stenosis in the left internal carotid artery and the patient subsequently underwent an endarterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Asavasopon et al, [54] reported a case of a 63-year-old female whose symptoms were consistent with VBI. The VAT was positive and the patient was referred to a physician for further diagnostic testing.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…In some of these publications, multiple patients were described, providing a total of 71 individual patient cases for review. 1,[4][5][6][7][8][12][13][14][15][16]17,18,[20][21][22][23][24][25][26][27][28][29][30][31][32]34,35,[37][38][39]41,42,44,[46][47][48][49][50][51][52][53][54][55]58,[60][61][62][63][64][65][66][67][68][69][70]…”
Section: T T Conclusionmentioning
confidence: 99%